Sociology for business : a practical approach - Joseph, Martin (Cambridge [England] : New York, 1989)
Introduction. Business and society. The social nature of work. Sociological insights into organizations. Industrial relations. The motivation to work...
Keywords: Business; Sociology; Sociology; Industrial sociology